2018
DOI: 10.13189/ujer.2018.060105
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Validity and Reliability on the Instructional Capacity Scale

Abstract: The aim of this study is to develop a valid and reliable measurement tool that can determine the instructional capacity, according to teacher opinions. In the academic year of 2016-2017, 1011 teachers working in the public high schools and vocational technical schools in Ankara participated in the study. The total number of items on the scale was 43. The scale is arranged in 5-point likert type scale format, with options ranging from 5 (Extremely) to 1 (Not at all). As a result of the analysis made, it consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…School leadership (SL). SL was measured through a 22-item scale developed by Leithwood (2012) and translated into Turkish by Yalçın and Atasoy (2021). The scale comprised four dimensions: setting direction, developing people, developing organization and improving the instructional program.…”
Section: Methodsmentioning
confidence: 99%
“…School leadership (SL). SL was measured through a 22-item scale developed by Leithwood (2012) and translated into Turkish by Yalçın and Atasoy (2021). The scale comprised four dimensions: setting direction, developing people, developing organization and improving the instructional program.…”
Section: Methodsmentioning
confidence: 99%
“…); step 3: factor rotation; (selection of rotational method, whether orthogonal rotations or oblique rotation); step 4: number of factors (such as the percentage of variance explained); and step 5: interpretation and labeling of factors (factor loadings and factor scores). This study selected the KMO statistics to use the measurement of the sample data as a value (.790), which indicated that it was appropriate to analyze the elements in good order [23]. Thus, based on the results, it was appropriate to proceed with a factor analysis to examine factors that affected the sustainable SHS development.…”
Section: Identification Of Factors Which Affected the Sustainable Devmentioning
confidence: 99%
“…Calculation of the reliability of model validity instruments and learning materials is based on the Cronbach's alpha formula, 2 = total variance(Yalçin & Ereş, 2018) …”
mentioning
confidence: 99%